2014
DOI: 10.1111/ceo.12317
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of methylprednisolone pulse therapy for Graves' ophthalmopathy

Abstract: A meta-analysis was performed to evaluate the efficacy of methylprednisolone pulse therapy for Graves' ophthalmopathy. Eight studies involving 376 patients were included. A higher effective rate was found for patients treated with intravenous glucocorticoids (IVGC) over oral glucocorticoids (OGC) (risk ratio [RR] = 1.48; 95% confidence interval [CI] = 1.18− 1.86). The combined IVGC and orbital radiotherapy (OR) was markedly more effective than OGC+OR (RR = 1.40; 95% CI = 1.11−1.77). IVGC resulted in an obvious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 46 publications
1
20
0
2
Order By: Relevance
“…Oral therapy is however more often associated to long term side effects, including hepatotoxicity, Cushing's syndrome, osteoporosis, glaucoma, and diabetes mellitus. Subsequent studies have shown that pulsed intravenous methylprednisolone (ivMP) is more effective (70-80 % responders) [16,20,39,[45][46][47] and has a better safety profile compared with oral prednisone [38,[48][49][50][51][52]. A wide range of ivMP treatment schedules have been used, with different cumulative doses administered (from 4.5 to 12 g) and occasionally associated with oral GC in the pause between each infusion or at the end of the protocol [16,20,39,[45][46][47]53].…”
Section: Reviewmentioning
confidence: 99%
“…Oral therapy is however more often associated to long term side effects, including hepatotoxicity, Cushing's syndrome, osteoporosis, glaucoma, and diabetes mellitus. Subsequent studies have shown that pulsed intravenous methylprednisolone (ivMP) is more effective (70-80 % responders) [16,20,39,[45][46][47] and has a better safety profile compared with oral prednisone [38,[48][49][50][51][52]. A wide range of ivMP treatment schedules have been used, with different cumulative doses administered (from 4.5 to 12 g) and occasionally associated with oral GC in the pause between each infusion or at the end of the protocol [16,20,39,[45][46][47]53].…”
Section: Reviewmentioning
confidence: 99%
“…In this double‐blind study, 159 patients with moderately to severely active GO were randomized to receive 12‐weekly infusions at a cumulative dose of 2.25, 4.98 or 7.47 g. None of the patients developed hepatotoxicity (defined as a fourfold or greater increase in serum liver enzymes). A subsequent meta‐analysis of eight randomized controlled trials that included 376 patients with GO revealed no liver‐related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Group A were treated with intravenously high-dose and group B with 25 An additional comparison between a high-and lowdose of MT pulse therapy in patients with GO was conducted by Bartalena et al 26 In this double-blind study, 159 patients with moderately to severely active GO were randomized to receive 12-weekly infusions at a cumulative dose of 2.25, 4.98 or 7.47 g. None of the patients developed hepatotoxicity (defined as a fourfold or greater increase in serum liver enzymes). A subsequent meta-analysis 27 of eight randomized controlled trials that included 376 patients with GO revealed no liver-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…La finalidad es disminuir el componente inflamatorio-infiltrativo. Se ha descrito un control de síntomas hasta en un 65-85% de los casos 27,28 .…”
Section: Actuaciones Terapéuticasunclassified